2017
DOI: 10.1016/j.jallcom.2016.12.184
|View full text |Cite
|
Sign up to set email alerts
|

Effects of magnetic field and rare earth addition on corrosion behavior of Al-3.0 wt% Mg alloy

Abstract: Effect of magnetic field and rare earth on the corrosion behavior of Al-3.0 wt.%Mg alloy in 3.5 wt.% NaCl solution was investigated by immersion test and electrochemical measurement. The results indicated that a horizontal magnetic field would increase the corrosion potential (E corr), impede the growth of pitting holes and reduce the corrosion current density i corr and corrosion rate of Al-3.0 wt.%Mg-xR E alloys. Proper content of R E would increase the corrosion resistance of Al-3.0 wt.%Mg alloys. Excessive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…This means that intermetallic fragmentation is the key factor in controlling the electrochemical properties of Al-10 wt% Ce alloy. This is in agreement with the available literature that discusses different Al-Ce alloys 16,18.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…This means that intermetallic fragmentation is the key factor in controlling the electrochemical properties of Al-10 wt% Ce alloy. This is in agreement with the available literature that discusses different Al-Ce alloys 16,18.…”
supporting
confidence: 93%
“…It has been reported that there is a galvanic cell between the intermetallic particles and the aluminum matrix. 18 This cell comes from the difference in potential between a/Al and of Al 11 Ce 3 phase, which encourages pitting of the surface at different positions. Considering the current study, fragmenting the intermetallic particles under the influence of ultrasonic vibrations was believed to affect the distribution and size of the pits.…”
Section: Microstructure Inside the Corroded Areamentioning
confidence: 99%
“…Therefore, the cathode is used for Tafel extrapolation in the present study, and the corrosion current density ( i corr ) is determined. The method used in the present study is also reported in Zhang et al [ 10,18 ] and Wang et al [ 24 ] The corrosion potential ( E corr ) and corrosion current density ( i corr ) are shown in Table 2. Less negative corrosion potential and lower corrosion current density of an alloy exhibit its superior corrosion resistance.…”
Section: Resultsmentioning
confidence: 90%
“…Recently, many efforts have been made to solve the problem of β‐Al 3 Mg 2 precipitation along the grain boundaries in the conventional Al–Mg alloys, including adjusting the processing technologies [ 8–10 ] and microalloying. [ 11–14 ] The microalloying additions can either modify the fraction, the composition, and the growth kinetics of the β‐Al 3 Mg 2 phase or introduce the additional Mg‐rich phases.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the corrosion resistance of unidirectional rolled magnesium alloy plate is the worst. In addition, in the middle and low frequency region of 3 (b) Bode diagram, the impedance modulus of sample B is the largest, and the impedance modulus of the material in the low frequency region is inversely proportional to its electrochemical activity, while the electrochemical activity is inversely proportional to the corrosion resistance of the material [19]. Therefore, the corrosion resistance of the magnesium alloy plate after cross rolling is the best.…”
Section: Potentiodynamic Polarization Curvementioning
confidence: 96%